2018
DOI: 10.1056/nejmoa1708423
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Therapy for the Prevention of Metachronous Gastric Cancer

Abstract: Patients with early gastric cancer who received H. pylori treatment had lower rates of metachronous gastric cancer and more improvement from baseline in the grade of gastric corpus atrophy than patients who received placebo. (Funded by the National Cancer Center, South Korea; ClinicalTrials.gov number, NCT02407119 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
485
4
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(520 citation statements)
references
References 35 publications
11
485
4
20
Order By: Relevance
“…Significant enrichment of Peptostreptococcus stomatis , Parvimonas micra , Streptococcus anginosus , Dialister pneumosintes , Slackia exigua, Clostridium colicanis and Fn and depletion of Helicobacterium was observed in gastric cancer, and alterations in bacterial diversity and abundance in patients with gastric cancer revealed a dysbiotic microbial community with prediction potential . Recently, incremental data has demonstrated that eradication treatment for H. pylori could reduce the risk of gastric cancer . Collectively, these studies indicate that gastric microbiota is involved in gastric carcinogenesis.With enormous microorganism at close proximity to the colonic epithelial cells, the involvement of gut microbiota in colorectal carcinogenesis is becoming clear.…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…Significant enrichment of Peptostreptococcus stomatis , Parvimonas micra , Streptococcus anginosus , Dialister pneumosintes , Slackia exigua, Clostridium colicanis and Fn and depletion of Helicobacterium was observed in gastric cancer, and alterations in bacterial diversity and abundance in patients with gastric cancer revealed a dysbiotic microbial community with prediction potential . Recently, incremental data has demonstrated that eradication treatment for H. pylori could reduce the risk of gastric cancer . Collectively, these studies indicate that gastric microbiota is involved in gastric carcinogenesis.With enormous microorganism at close proximity to the colonic epithelial cells, the involvement of gut microbiota in colorectal carcinogenesis is becoming clear.…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…It was also again confirmed in a mega Chinese controlled trial that after endoscopic resection of early gastric cancer patients there were lower rates of metachronous gastric cancer, together with more improvement of corpus mucosal atrophy if H. pylori was eradicated [6] (Fig. 2).…”
mentioning
confidence: 72%
“…Median follow-up time was 5.9 years with meta-chronous lesions occurring in 14 patients (7.2%) in the treatment group and 27 (13.4%) in the placebo group. This demonstrated a 50% risk reduction by eradication treatment (HR 0.50; 95% CI 0.26-0.94, p = 0.03) [121]. Knowledge of further relevant factors that influence the effect of H pylori eradication is expected from the interventional study that is currently being undertaken in the Chinese province of Linqu with international support [122].…”
Section: H Pylori Eradicationmentioning
confidence: 90%
“…This had been confirmed in a 2016 meta-analysis of 10 studies including 5,881 patients reporting a risk reduction of more than 60% (OR 0.39; 95% CI 0.259-0.593; p < 0.001) [120]. And final clarity on this issue was given by a recently published prospective double-blind, placebo-controlled randomised trial on 470 patients undergoing endoscopic resection of early gastric cancer or HGD [121]. Median follow-up time was 5.9 years with meta-chronous lesions occurring in 14 patients (7.2%) in the treatment group and 27 (13.4%) in the placebo group.…”
Section: H Pylori Eradicationmentioning
confidence: 91%